Complete chloroplast genome of an Endangered mangrove plant Hernandia nymphiifolia (C. Presl) Kubitzki (Hernandiaceae). Issue 1 (2nd January 2018) - Zhang, Ying; Zhang, Jing-Wen; Jin, Ying-Hong; Li, Dong-Lin; Diao, Xiao-Ping
Abstract: This study presents the chloroplast genome of Hernandia nymphiifolia (C. Presl) Kubitzki (Hernandiaceae) one Endangered mangrove species in China, which was assembled and analyzed by de novo assembly using whole chloroplast genome sequencing data. The accessing ID of reference sequence was MG838431. The size of the complete chloroplast genome was 157, 762 bp in length with a large single-copy region (LSC) of 86, 641 bp, a small single-copy region (SSC) of 18, 603 bp, and two inverted repeat regions (IRS) (26, 260 bp). The GC content of H. nymphiifolia is 39.3%. From the chloroplast genomes, 133 genes, including 83 protein-coding genes, 42 tRNA genes, and 8 rRNA genes, were predicted. Among them, 17 genes occur in IRS, containing 6 protein-coding genes, 7 tRNA genes and 4 rRNA genes. The phylogenetic analysis with 10 eudicots species and rice as the outgroup revealed that H. nymphiifolia was clustered with 6 Ranunculales species.